Flexible composite felt of electrospun TiO2 and SiO2 nanofibers infused with TiO2 nanoparticles for lithium ion battery anode. (1st February 2016) - Wang, Xiaoxu; Xi, Min; Wang, Xinhou; Fong, Hao; Zhu, Zhengtao
Graphical Abstract: Highlights: Composite felt of electrospun TiO2 /SiO2 nanofibers and TiO2 nanoparticles was prepared. Mechanically flexible/robust felt was evaluated as Li-ion battery anode. Li-ion battery based on the TiO2 felt showed high capacity and good rate capability. Flexible composite felt retained high capacity after bending test. Abstract: A flexible felt consisting of electrospun anatase TiO2 and amorphous SiO2 nanofibers together with anatase TiO2 nanoparticles was explored as an innovative anode material for lithium ion battery. The electrochemical characterization of the half-cell of the composite felt ( vs. Li metal) showed that the felt had a high initial discharge capacity of 170 mAh/g and an excellent rate capability; furthermore, the capacity was retained at 84% of initial value after 100 cycles at fast charge/discharge rate of 1 A/g. The binder-free composite felt maintained superior flexibility/robustness and good electrochemical performance after 5, 000 continuous bending cycles.